Konsep Dan Strategi Pemasaran Diperlukan untuk Menyikapi Persaingan Bisnis Perusahaan - Kelvin Pedro Gamalael; Angel Frilyaningrum; Tri Esti Rahayuningtyas; Choerul Umam (Universitas Dian Nuswantoro, 2022)
The level of business competition in this era of globalization occurs very quickly and tightly, this makes every business actor, especially companies, must be able to find a way out. One aspect that really needs attention is the marketing aspect. With this marketing concept and strategy the company can continue to exist in carrying out its business activities. The company is also expected to be able to face growing competition and be able to achieve the desired success. The purpose and intent of this research is to find out and analyze several concepts and good marketing strategies in order to address the current business competition. The research method used is a qualitative approach which is carried out by taking secondary data sources from previous references such as literature. , various journals, as well as related documents according to the study and research themes and analyzed. Through this research, it is explained that the business world really needs good marketing concepts and strategies in order to be able to compete. Of course, careful preparation in planning the concept and marketing strategy is needed. Thus, each concept and strategy produced is able to provide many benefits for both the Company and consumers.